Proceedings of the International Conference of Democratisation in Southeast Asia (ICDeSA 2019) 2019
DOI: 10.2991/icdesa-19.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiscal Desentralization and Region-wide Corruption Level in Indonesia

Abstract: Many parties suspect that there is an in-between relationship of fiscal decentralization and the corruption level in the regencies and city. This study aims to examine the effect of fiscal decentralization on the city-wide corruption level in Indonesia. This study used the General Allocation Fund (Dana Alokasi Umum or DAU) of the regency and city, age of regency and city, and location of regency and city as the control variables. The population of this research is all regencies and cities in Indonesia. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Being viewed from the corruption case data, the regional government ranks the most corrupt state agency. This statement is supported Anan [5] and Ulum et al [38] explaining that the cause of the high number of corruption cases in Indonesia is caused by the implementation of fiscal decentralization. Thus, the formulated the hypothesis as follows:…”
Section: Fiscal Decentralizationsupporting
confidence: 61%
See 2 more Smart Citations
“…Being viewed from the corruption case data, the regional government ranks the most corrupt state agency. This statement is supported Anan [5] and Ulum et al [38] explaining that the cause of the high number of corruption cases in Indonesia is caused by the implementation of fiscal decentralization. Thus, the formulated the hypothesis as follows:…”
Section: Fiscal Decentralizationsupporting
confidence: 61%
“…The serious agency problems depend on the efforts of internal supervisory agencies, external oversight, the power of political leadership in controlling government at the lower levels, and the level of difference in goals between principle and agent [6]. According to Anan [5], decentralization is one of the factors contributing to the high corruption in local governments. The high number of corruption cases in local governments demonstrates the need for oversight in order to minimize corruption [14].…”
Section: Law Enforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…The Effect of Fiscal Decentralization towards Corruption Level: Blackburn et al (2006) stated that the delegation of authority by the central government to local governments causes an agency problem, which can result in corruption practice. This statement is supported by a previous study which states that decentralization is one of the factors behind the prevalence of corruption in local governments (Anan, 2019;Ko & Zhi, 2013). However, Shah (2006) states that decentralization can strengthen public accountability by involving the people to monitor the performance of local governments and demand corrective actions, including demanding authorized parties to mitigate corruption and its causes.…”
Section: Hypothesis and Conceptual Frameworkmentioning
confidence: 78%
“…The data shows that the governmental institution with the highest prevalence of corruption cases are district/city local governments. Anan (2019) stated that decentralization is one of the causes of the high levels of corruption in local governments of Indonesia. Previous studies have also shown that fiscal decentralization has a significant effect towards corruption levels (Anan, 2019;Dong & Torgler, 2013;Fisman & Gatti, 2002).…”
Section: P R D a N D P R D K E M E N T E R I A N / L E M B A G A B mentioning
confidence: 99%